Enhancing E-Commerce System Scalability Through Event-Driven Architecture with RabbitMQ and Docker - Rifqi Ramdhani; Alun Sujjada; Nugraha Nugraha (Komunitas Dosen Indonesia, 2025)
The rapid expansion of e-commerce in Indonesia has intensified the demand for highly scalable and responsive systems, especially during high-traffic periods. Traditional architectures that rely on synchronous Remote Procedure Call (RPC) models often experience performance bottlenecks, which can degrade user experience during peak load. To address this limitation, this study evaluates the use of an Event-Driven Design (EDD) architecture to improve system scalability and responsiveness. The objective is to compare the performance of RPC and EDD architectures using the